Evaluación del efecto del macerado de chocho (Lupinus mutabilis Sweet) para el control de las principales plagas en el cultivo de chocho en la parroquia de Chugchilán de la provincia de Cotopaxi, 2021-2022. - Ayar Arawi, Guanotuña Chusin (2022)
The present research project was carried out in the Chugchilán Parish, Sigchos Canton, in the Province of Cotopaxi, at a height of 3261 meters above the sea level with the aim of determining the evaluation of the effect of lupine (Lupinus mutabilis Sweet) maceration on the control of the main pests in lupine cultivation. The specific objectives of this investigation were: Determine the best treatment with the application of lupine maceration and get the data of the population dynamics of the pests of each treatment, elaborating a Completely Random Block Design (DBCA), with six treatments, each treatment with three repetitions giving a total of eighteen experimental units. For the analysis of the data, we used the statistical software Infostat (IS). The effect of the variable T5 (Chemical chlorcyrin) on the average control of the larvae and insects that was carried out in the analysis of variance (ADEVA), the results of this study revealed that in the phenological stages of development 56 DDS was obtained an average of 6.33 larvae and one insect, in the flowering stage at 86 DAS with one larva and one insect and in the phenological stage of sheathing at 147 DAS with 3 larvae and 2 existing insects. Subsequently, the best control with the treatment with lupine macerates was the T3 (100g, tender Lupinus mutabilis) showing that in the phenological stages of development 56 DDS an average of 13.33 larvae and 2 insects were obtained, in the flowering stage at 86 DAS with 6 larvae and 1.33 insects and finally in the phenological stage of sheathing at 147 DAS with an average of 12.33 larvae and 2.67 existing insects, and the other maceration treatment of chocho was the T1 (100g. Dry Lupinus mutabilis) in the phenological stages of development 56 DDS an average of 14 larvae and 2.33 insects were obtained, in the flowering stage at 86 DDS with an average of 6.67 larva and 1 .67 insects and in the phenological stage of sheathing at 147 DDS with 8.67 larvae and 3.33 existing insects.